2021
DOI: 10.1007/s10534-021-00349-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron on Chilean Alexandrium catenella growth and paralytic shellfish toxin production as related to algal blooms

Abstract: The dinoflagellate Alexandrium catenella is a well-known paralytic shellfish toxin producer that forms harmful algal blooms (HABs) worldwide. Blooms of this species have repeatedly brought severe ecological and economic impacts to Chile, especially in the southern region, where the shellfish and salmon industries are world-famous. The mechanisms of such HABs have been intensively studied but are still unclear. Nutrient overloading is one of the often-discussed drivers for HABs. The present study used the A. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Decrease in Fe leads to increased PSP toxin content and PSP toxicity per cell, and changes in the PSP toxin profile of Alexandrium tamarense [212]. Interestingly, a gradient of Fe concentrations tested on A. catenella and A. minutum revealed the highest toxin levels were observed not in the lowest Fe treatment tested but at the most optimal [197,209]. Comparison between the three studies shows that the highest PSP toxin concentration per cell was observed at 1 nmol L −1 Fe for A. tamarense, while it was at 1000 nmol L −1 Fe for A. catenella [209,212].…”
Section: Iron (Fe)mentioning
confidence: 98%
See 3 more Smart Citations
“…Decrease in Fe leads to increased PSP toxin content and PSP toxicity per cell, and changes in the PSP toxin profile of Alexandrium tamarense [212]. Interestingly, a gradient of Fe concentrations tested on A. catenella and A. minutum revealed the highest toxin levels were observed not in the lowest Fe treatment tested but at the most optimal [197,209]. Comparison between the three studies shows that the highest PSP toxin concentration per cell was observed at 1 nmol L −1 Fe for A. tamarense, while it was at 1000 nmol L −1 Fe for A. catenella [209,212].…”
Section: Iron (Fe)mentioning
confidence: 98%
“…Cu, Sn (as butyltin) [206] Cu, Cd [207] Zn, Pb [208] Fe [209] Co (Vitamin B 12 ) [204] Alexandrium minutum Fe, Cu [197] Se [210] Cu [211] Co (Vitamin B 12 ) [204] Table 2. Cont.…”
Section: Species Metals Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, a high concentration of Fe reduced the total toxicity levels to 10.4 fmol/cell (10 µM) compared to 33.6 fmol/cell (1 µM) [80]. This suggests that Fe influences the particular growth rate, cellular biochemical composition, and the synthesis of the toxins in the dinoflagellate Alexandrium [48]. In addition, Cu induced toxin production via modulating the growth rate and photosynthetic activity concentration dependently in dinoflagellate A. minutum [82].…”
Section: Miscellaneousmentioning
confidence: 98%